Light-evoked deformations in rod photoreceptors, pigment epithelium and subretinal space revealed by prolonged and multilayered optoretinography - Tan, Bingyao (2024)
Phototransduction involves changes in concentration of ions and other solutes within photoreceptors and in subretinal space, which affect osmotic pressure and the associated water flow. Corresponding expansion and contraction of cellular layers can be imaged using optoretinography (ORG), based on phase-resolved optical coherence tomography (OCT). Until now, ORG could reliably detect only photoisomerization and phototransduction in photoreceptors, primarily in cones under bright stimuli. Here, by employing a phase-restoring subpixel motion correction algorithm, which enables imaging of the nanometer-scale tissue dynamics during minute-long recordings, and unsupervised learning of spatiotemporal patterns, we discover optical signatures of the other retinal structures' response to visual stimuli. These include inner and outer segments of rod photoreceptors, retinal pigment epithelium, and subretinal space in general. The high sensitivity of our technique enables detection of the retinal responses to dim stimuli: down to 0.01% bleach level, corresponding to natural levels of scotopic illumination. We also demonstrate that with a single flash, the optoretinogram can map retinal responses across a 12° field of view, potentially replacing multifocal electroretinography. This technique expands the diagnostic capabilities and practical applicability of optoretinography, providing an alternative to electroretinography, while combining structural and functional retinal imaging in the same OCT machine.